ChemInform Abstract: Base‐Free Photoredox/Nickel Dual‐Catalytic Cross‐Coupling of Ammonium Alkylsilicates. Issue 29 (June 2016) - Jouffroy, Matthieu; Primer, David N.; Molander, Gary A.
Abstract: Ammonium organobis(catecholato)silicates are introduced as valuable 1° and 2° alkyl radical precursors in dual‐catalytic cross‐coupling reactions with (hetero)aryl bromides.